Impact of histological variants on outcomes in patients with urothelial carcinoma treated with pembrolizumab: a propensity score matching analysis. (6th July 2021) - Kobayashi, Mizuki; Narita, Shintaro; Matsui, Yoshiyuki; Kanda, Souhei; Hidaka, Yu; Abe, Hiroyasu; Tsuzuki, Toyonori; Ito, Katsuhiro; Kojima, Takahiro; Kato, Minoru; Hatakeyama, Shingo; Matsushita, Yuto; et al.
Abstract : Objectives: To assess the impact of histological variants on survival and response to treatment with pembrolizumab in patients with chemo‐resistant urothelial carcinoma (UC). Patients and Methods: The medical records of 755 patients with advanced UC who received pembrolizumab were reviewed retrospectively. Patients were classified into pure UC (PUC) and each variant. Best overall response (BOR) and overall survival (OS) were compared between the groups using a propensity score matching (PSM). Results: Overall, 147 (19.5%) patients harboured any histological variant UC (VUC). After PSM, there were no significant differences in the objective response rate (ORR, 24.5% vs 17.3%, P = 0.098) or disease control rate (DCR, 36.7% vs 30.2%, P = 0.195) when comparing patients with any VUC and PUC. Furthermore, any VUC, as compared with PUC, was associated with a similar risk of death (hazard ratio [HR] 0.90, 95% confidence interval [CI] 0.68–1.20; P = 0.482). Squamous VUC, which was the most frequent variant in the cohort, had a comparable ORR, DCR and OS as compared with PUC or non‐squamous VUC. The patients with sarcomatoid VUC ( n = 19) had significantly better ORR (36.8%, P = 0.031), DCR (52.6%, P = 0.032), and OS (HR 0.37, 95% CI 0.15–0.90; P = 0.023) compared to patients with PUC. Conclusions: The presence of variant histology did not seem to affect BOR or OS after pembrolizumab administration in patients with chemo‐resistant UC. The patients with sarcomatoid VUC achieved favourable responses and survival rates compared to PUC.